Prevalence, Spinal Alignment, and Mobility of Lumbar Spinal Stenosis with or without Chronic Low Back Pain: A Community-Dwelling Study. (5th May 2011) - Miyakoshi, Naohisa; Hongo, Michio; Kasukawa, Yuji; Ishikawa, Yoshinori; Shimada, Yoichi
Abstract : Although lumbar spinal stenosis (LSS) occurs almost universally with aging, little is known regarding its actual prevalence and relationships to chronic low back pain (CLBP) in the general population. The presence of CLBP in subjects with LSS may have negative impacts on spinal alignment and mobility. This study evaluated the prevalence of LSS using a self-administered, self-reported history questionnaire in 630 community-dwelling individuals ≥50 years old. Subjects with LSS were further divided into LSS+CLBP and LSS alone groups, and spinal alignment and mobility were compared using a computer-assisted device. Prevalence of LSS was 10.8% in this cohort. Subjects in the LSS+CLBP group (n = 46 ) showed a significantly more kyphotic lumbar spinal alignment with limited lumbar extension (P < .05 ), resulting in a stooped trunk compared to subjects in the LSS alone group (n = 22 ). However, no significant difference in spinal mobility was seen between groups.